Professional meeting of librarians in the North of Republic of Moldova in USARB Librarianship Departmental Center (Confluenţe Bibliologice, 2018)
On April 27, 2018, the Departmental Library Center of USARB Scientific Library organized a professional meeting of the librarians from the educational system of the Republic of Moldova, attended by 40 specialists - responsible for the activity of school libraries and technical vocational education in OLSDH, school librarians, colleges and vocational schools. During the meeting, important professional events, the achievements of the Departmental Librarianship Center (DLC) in 2017 and the outlook in 2018 were reviewed.
Keywords: Departmental Librarianship Center; professional events; international projects